Clinical Characteristics and Complications of Polypectomy of Colorectal Polyps: An Observational study from Western Nepal - Thapa, Jiwan; Thapa, Suresh; Thapa, Anuja Bhandari (Journal of Bharatpur Hospital, 2026)
BackgroundColorectal polyps are precursor lesion for colorectal cancer. Polyps are detected and managed by polypectomy during colonoscopy. Polypectomy requires endoscopic expertise and adequate resources but is associated with complications. The objective of this study was to characterize colorectal polyps and assess the complications of polypectomy at our centre.MethodsThis is a retrospective, cross sectional, hospital based observational study done during January 2021-December 2024 at Fewacity Hospital Pvt. Ltd., Pokhara, Nepal after an ethical clearance. Detected colorectal polyps were characterized by number, location, size and managed by polypectomy during colonoscopy. Recommended polypectomy techniques were applied and complications managed appropriately. Data was entered in Microsoft Excel 2024 and descriptive analysis was done. ResultsRectal polyps (23.5%) were commonest followed by sigmoid polyps. Inflammatory (42%) followed by tubular adenoma (35%) were common histological types identified. Large size polyps (>10mm) comprised of 21%. Cold snare was common polypectomy technique applied (68%). Assisted polypectomy technique was required in 37 patients (11%). Overall complications developed in nine patients (2.7%) with polypectomy. Delayed bleeding was the commonest complication reported among 7 patients (2.8% in hot snare polypectomy and 0.8% in cold snare polypectomy) and was managed with endoclips application.ConclusionsColorectal polyps were detected in 19% of patients with rectum as commonest location and inflammatory as common histological subtype. Post polypectomy bleeding was the commonest complication and was managed by endoscopic techniques.